PENGARUH PERSEDIAAN, INVESTMENT OPPORTUNITY SET DAN KURS VALUTA ASING TERHADAP RETURN SAHAM - Siska Julian; Syamsul Huda (FKIP Unswagati, 2023)
This study aims to determine and describe the effect of inventory, investment opportunity set and foreign exchange rates.The population in this study includes all automotive and component sub-sector companies listed on the Indonesian Stock Exchange for the 2018-2021 period. Determination of the sample used in this study as a representative form of the population using a purposive sampling technique. The use of data analysis techniques in this study is descriptive and verification analysis. The selected sample data in this study were then tested using a multiple linear regression analysis model.The results of the research that has been done inform that inventory has no effect on stock returns. investment opportunity set has a significant effect on stock returns.foreign exchange rates have no effect on stock returns inventory, investment opportunity set and foreign exchange rates simultaneously have no significant effect on stock returns. The result of testing the analysis of the coefficient of determination is that the value of the coefficient of determination (Adjusted R Square) This value informs that changes in inventory, investment opportunity sets and foreign exchange rates affect changes in stock returns by 13.80% influenced by other variables outside this study.